REPRODUCTIVE PERFORMANCE OF NILAGIRI AND SANDYNO EWES - KUMAR, R ANIL; CHANDRAHASAN, C; SELVARAJU, M; DINAKARAN, A MANICAVASA (The Indian Journal of Animal Reproduction, 2023)
The tupping percentage, lambing percentage, litter size, twinning percentage were worked out from the reproductive records 1993-2002) available at Sheep Breeding Research Station, Sandynallah, Nilgiris District. Nilagiri ewes were superior to Sandyno ewes in tupping percentage (7 4.60 ± 0. 7 4 vs. 60.30 ± 0.65 per cent), lambing percentage (92.1 0 ± 0.85 vs. 90.00 ± 0.83 per cent), litter size (1.12 ± 0.01 and 1.05 ± 0.01) and twinning percentage (12.51 and 6.43 percent). The ewes from both breeds had higher reproductive performance during main t,reeding season than off breeding season (Tupping percentage: 92.10 ± 0.57 and 36.30 ± 0.85 per cent, lambing percentage: 94.60 ± 0.58 and 88.00 ± 1.20 per cent and litter size: 1.10 ± 0.01 and 1.07 ± 0.01 in main breeding season and off breeding season respectively). The age of ewes at breeding had significant effect on tupping percentage, lambing percentage and litter size at birth. Ewes aged from 3½ - 5½ years performed at their best and the reproductive performance declined after 6½ years.